Sublinear association between cortical thickness at the onset of the adult lifespan and age-related annual atrophy parallels spatial patterns of laminar organization in the adult cerebral cortex - Bruno Hebling Vieira; Carlos Ernesto Garrido Salmon (NeuroImage: Reports)
Brain aging is a complex process, entailing alterations at the most diverse levels of brain structure and functioning. On the macroscopical scale, gray matter atrophy is one of its most prominent markers, but it remains to be elucidated why some regions are more affected by it than others. In this work, we aimed to explore how age affects the morphometry of cortical structures, and specially the relationship between atrophy and the initial state of regions. To this end, anatomical T1-weighted images from 612 subjects aged 18–85 years were employed. Atlas-based cortical morphometric estimates were obtained. Our results show that, whilst there is no obvious shared pattern between the initial surface area of cortical regions at eighteen years and their yearly rate of decay, for cortical thickness there is enough evidence to suggest thicker regions at eighteen years of age also present higher yearly rates of thinning, although yearly percentages are proportionately smaller. Our analyses reveal that neocortical regions tend to conform to this trend, where agranular cortices experience higher atrophy levels than granular cortices, contrasting a few non-pure neocortical regions that do not follow this trend, highlighting parallels between brain evolution and brain aging.